Interspecific niche overlap and climatic associations of native Quercus species in the Zagros forests of Iran - Maedeh Sadeghi; Mansoureh Malekian; Mostafa Tarkesh Esfahani (Global Ecology and Conservation, 2024)
In the arid regions surrounding southwestern Asia, oak trees play an important role in the environment by conserving water and preserving soil and supporting wildlife. There are concerns for the health and continued productivity of these forests, and there is a widespread oak decline. In this study, ecological niche modeling (ENM) and multivariate principal component analysis (PCA) were used to determine the environmental variations among Quercus brantii, Q. infectoria, and Q. libani in the Zagros forests of western Iran. Based on the area under the curve (AUC > 0.9) and the true skill statistic (TSS > 0.8), three algorithms, including random forest (RF), maximum entropy (MaxEnt), and maximum picking neural net (MAXnet), were used in an ensemble approach to explore the most important environmental variables within the projected suitable habitat of each species. Environmental variables related to climate, including annual precipitation (bio12) and annual mean temperature (bio1), were among the most important drivers of habitat suitability for oak species. The results illustrated that suitable areas for Q. infectoria and Q. libani often occur in the northern parts of the Zagros, which are humid and cooler than the southern areas. The results suggested that Q. brantii has a higher tolerance for harsh conditions in Zagros and therefore inhabits almost all areas of Zagros, including the southern parts. The climatic overlap between pairs of species was found to be significant based on equivalency and similarity tests, suggesting that the environmental conditions of the two species compared are more similar than would be expected by chance. The gap analysis for the three oak species revealed that only a few protected areas currently exist within their suitable habitats, with most of the highly suitable habitats located on non-protected lands, particularly for Q. libani and Q. infectoria. In addition, deforestation is known to sometimes occur within the boundaries of protected areas. Improving the level of protection by upgrading the current protected areas to national parks can help with conservation.